Fuzzy Linear Programming Techniques: - S.S., Dr. Zampalwad (Journal of Global Research in Mathematical Archives(JGRMA), 2015)
The fuzzy set theory has been applied in many fields, such us operations research, control theory and management sciences, business organization etc. In particular an application of this theory in decision making problems is linear programming problems with fuzzy numbers. In this study, we present a new method for solving fuzzy number linear programming problems, by use of linear ranking function. Keywords and Phrases: Fuzzy number linear programming, ranking function. 2000 Mathematics Subject Classification: 03B52, 68T27, 68T37, 94D05.